Transcriptome analysis discloses antioxidant detoxification mechanism of Gracilaria bailinae under different cadmium concentrations and stress durations - Li, Zailiang; Li, Yangmei; Xie, Enyi; Shen, Yuchun (Frontiers in Plant Science, 2024)
To remedy Cd pollution in the ocean, macroalgae are used as a bioremediation tool because of their ability to absorb and accumulate Cd. Gracilaria bailinae has high economic and ecological value and can survive in Cd contaminated waters; however, the underlying molecular mechanisms remain unclear. In this study, physiological and biochemical indexes were analyzed after 1, 3, 5, or 7 days of Cd2+ exposure; further, the transcriptome of G. bailinae was examined after a 7-day exposure to a Cd2+ culture environment with Cd levels of 0 mg L-1 (cd1, control), 1 mg L-1 (cd2, low concentration), and 2.5 mg L-1 (cd3, high concentration). The results showed that in the cd2 group, G. bailinae maintained a stable RGR that did not differ significantly (P > 0.05) from that of the cd1 group. However, the soluble protein and MDA contents, as well as the activities of SOD, CAT and POD, were significantly increased (P< 0.05) compared to the cd1 group. No significant differences (P > 0.05) were found among the different Cd2+ stress durations. In contrast, compared with the cd1 group, the RGR, soluble protein content, SOD, CAT, and POD activities were significantly decreased (P< 0.05), while the MDA content was significantly increased (P< 0.05) in the cd3 group. Furthermore, significant differences (P< 0.05) were observed among the various tested Cd2+ stress durations within the cd3 group. Compared to the cd1 group, a total of 30,072 DEGs and 21,680 were identified in the cd2 and cd3 treatments, respectively. More up-regulated genes were found in cd2 group than in cd3 group. GO enrichment analysis showed that these genes were related to peptidase activity, endopeptidase activity, ion transport, peptide biosynthetic and metabolism. In addition, DEGs related to histidine metabolism and the stilbene, diarylheptane, and gingerol pathways were significantly up-regulated in the cd2 group compared to the cd3 group, which resulted in enhanced activities of antioxidant enzymes and promoted cell wall regeneration. The results of this study reveal the response mechanism of G. bailinae to Cd2+ stress, providing valuable insights for assessing the bioremediation potential of G. bailinae for Cd-contaminated waters.